Experimental procedures, influencing parameters, and future prospects of geological sequestration of carbon dioxide - Dai, Kun; Xia, Yan; Yuan, Guangjie; Liu, Tianen; Zhang, Hong; Song, Hengyu; Yuan, Haowei (Frontiers in Earth Science, 2025)
Carbon capture and storage (CCS) is receiving increasing attention as a technology to mitigate the increasingly serious impacts of climate change. This review explains the CCS process, providing details of important factors influencing its performance, current barriers to its widespread commercialization, and potential pathways for advancement. Integrated data analysis is applied to investigate the multiple factors affecting the storage capacity of CCS sites, including the geological properties of reservoir sites, physicochemical characteristics of CO2, and petrophysical features of rocks. We also review recent developments in CCS technology. Our findings will help guide the precise design of CCS systems and the control of their parameters to improve performance and reliability. Although practical obstacles such as cost and public acceptance remain before CCS can be implemented at a large scale, progress continues to be made in terms of monitoring technologies, evaluation methodologies, and CO2 capture/conversion strategies. In addition, ongoing and future research avenues are also discussed, which include the development of novel monitoring technologies, new possibilities for evaluating long-term storage impacts, and improvements to CO2 capture and conversion methods. The study offers valuable insights into the emerging technology of CCS and may aid future improvement to, for example, its commercial viability, which could aid progress toward international carbon neutrality ambitions.